2012
DOI: 10.1097/meg.0b013e328351097f
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose heparin in the prevention of post endoscopic retrograde cholangiopancreatography pancreatitis

Abstract: One of the most frequent and serious complications of endoscopic retrograde cholangiopancreatography (ERCP) is acute pancreatitis. The aim of this study was to evaluate the preventive effect of low-dose heparin (unfractionated or low-molecular-weight heparin) on post-ERCP pancreatitis (PEP) and its side-effects by a systematic review and meta-analysis of clinical trials. Searching PubMed and EMBASE, up to August 2011, two independent reviewers systematically identified prospective clinical trials detecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
0
16
0
2
Order By: Relevance
“…Moreover, heparin in a complex with antithrombin or heparin cofactor II is able to reduce activity of trypsin and chymotrypsin as well as the conversion of trypsinogen into trypsin [171,172]. Various experimental studies have shown the anti-inflammatory effect of heparin, administered both in a protective and therapeutic manner in AP [171,173,174,175,176,177,178]. Earlier studies have been summarized by Hackert et al in 2004 [179].…”
Section: Therapeutic Effects Of Anticoagulants In Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heparin in a complex with antithrombin or heparin cofactor II is able to reduce activity of trypsin and chymotrypsin as well as the conversion of trypsinogen into trypsin [171,172]. Various experimental studies have shown the anti-inflammatory effect of heparin, administered both in a protective and therapeutic manner in AP [171,173,174,175,176,177,178]. Earlier studies have been summarized by Hackert et al in 2004 [179].…”
Section: Therapeutic Effects Of Anticoagulants In Acute Pancreatitismentioning
confidence: 99%
“…Neither of the studies demonstrated reduced AP or SAP ratios in the treatment groups. A meta-analysis [177] performed in 2011 that included the four trials cited above (1438 patients in total) did not show significant benefit of prophylactic heparin in prevention of post-ERCP pancreatitis (relative risk 0.67, 95% confidence interval 0.44–1.03, p = 0.07) or post-ERCP SAP (relative risk 0.62, 95% confidence interval 0.15–2.60, p = 0.51). There were no differences between unfractioned and low molecular weight heparin.…”
Section: Therapeutic Effects Of Anticoagulants In Acute Pancreatitismentioning
confidence: 99%
“…A meta-analysis of four trials (1438 patients) demonstrated no benefit for prophylactic heparin in prevention of post-ERCP pancreatitis [83] . Magnesium sulphate (intravenous) is currently being studied as a calcium-antagonist and hence, a prophylactic agent against post-ERCP pancreatitis [84] .…”
Section: Inhibition Of Protease Activitymentioning
confidence: 99%
“…Other drugs that have been evaluated include glucocorticoids, 76 interleukin (IL)-10, 77 heparin, 78 antioxidants, [79][80][81] and agents that lower the pressure of sphincter of Oddi, such as botulinum toxin, lidocaine, and nifedipine [82][83][84][85] . The trials on these drugs did not show clinical efficacy in lowering the incidence of PEP.…”
Section: Drugs Without Proven Efficacymentioning
confidence: 99%